Seasonal dynamics of four cryptic species of Crepidostomum spp. in a subarctic lake in Northern Norway - Drage, Kristine (UiT The Arctic University of Norway, 2023)
The function of parasites in ecosystems is often overlooked, and there is a general lack of knowledge about parasite biodiversity down to species levels, especially for cryptic species. This study looks at the seasonal dynamics of four cryptic species of the trematode Crepidostomum spp. in Lake Takvatn, Northern Norway. Samples were collected between June 2017 and May 2018, and a total of 560 specimens of Crepidostomum spp. were sequenced in this study. The species were identified by phylograms based on novel cytochrome c oxidase subunit 1 (CO1) sequences. The species from Takvatn grouped into four distinct species-level lineages: C. farionis, C. pseudofarionis, C. metoecus and C. brinkmanni. The dominant species were C. farionis and C. brinkmanni, while C. pseudofarionis and C. brinkmanni were much rarer. The species showed clear dissimilarity in host distribution. Brown trout had a more diverse infracommunity than Arctic charr, and comprised all four species, while Arctic charr was mainly parasitised by the two dominant species. The species showed some variance in seasonality. The dominant species had a peak in frequency during autumn and winter, while the rarer species displayed a peak in frequency during autumn. In general, juveniles were mostly found in winter. The seasonal patterns of the Crepidostomum species could be linked to the seasonality of their intermediate hosts and the seasonal dietary shifts of their final hosts. Infection of C. farionis and C. metoecus could be connected to the fish preying upon the second intermediate host Gammarus lacustris during autumn and winter, especially for Arctic charr. Infection with C. pseudofarionis and C. brinkmanni for brown trout is likely due to the trout preying upon the second intermediate hosts mayflies and stoneflies over the summer months. The two rarer species might be more prevalent in Takvatn than indicated in this study due to the lack of samples of brown trout during spring and summer.